Developmental rates of the Lappet Moth Streblote panda Hubner (1820)(Lepidoptera: Lasiocampidae) at constant temperatures - Calvo, D.=700 1 Molina, J.M.
(Es, En)
ilus., 28 ref.
Keywords: LEPIDOPTERA; LASIOCAMPIDAE; INSECTA; DESARROLLO BIOLOGICO; DESARROLLO ESTACIONAL; FENOLOGIA; TEMPERATURA; ESPAÑA; TASA DE CRECIMIENTO